Analisis Nilai Pendidikan Islam dalam Buku “Jika Tuhan Maha Kuasa Kenapa Manusia Menderita?” Menyikapi Krisis Iman Gen Z - Suryawijaya, Achmad (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study analyzes the Islamic educational values contained in Ulil Abshar Abdalla’s book “Jika Tuhan Maha Kuasa, Kenapa Manusia Menderita?” (If God Is Almighty, Why Do Humans Suffer?) as a theological response to Generation Z’s faith crisis in the digital era. Using a qualitative descriptive and literature-based approach, this research explores how the concepts of tauhid (divine unity) and ikhlas (sincerity) are presented as essential values in strengthening spiritual awareness and understanding human suffering from an Islamic perspective. The findings reveal that both values serve as the foundation for developing reflective and humanistic Islamic education, guiding individuals to interpret suffering as a means of spiritual growth rather than divine punishment. The study concludes that integrating tauhid and ikhlas within Islamic education can foster resilience, meaning, and faith maturity among modern Muslim youth.